PENGARUH KEMAMPUAN AKUNTANSI MANUAL TERHADAP HASIL BELAJAR MYOB PADA MATA KULIAH KOMPUTER AKUNTANSI MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS RIAU - Hutabarat, Elfrida; Gusnardi, Gusnardi; RM Riadi, RM Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The emergence of the problem that the gap of hope and facts in the field of accounting computer learning results that use MYOB program Acoounting can be said to be less satisfactory among the students of economic education, thus raises the question the cause of the subject occurred, besides the previous research is also not consistent so that researchers interested in researching the influence the ability of manual accounting on learning outcomes MYOB on the student computer accounting courses Economic education of University of Riau. The purpose of this study is To determine the effect of manual accounting ability on MYOB learning outcomes in computer accounting courses of economics education students. The population in this study is all students of economic education Faculty of Teacher Training and Education University of Riau force 2014 which amounted to 95 students. This research uses quantitative approach, that is to know the influence of independent variable to dependent variable, then the data is tabulated and analyzed using statistic with the help of SPSS. Simple regression analysis performed shows that the ability of manual accounting has a significant effect on learning results MYOB student education economy..Keywords: Computer accounting, MYOB, Manual Accounting